Different Types of Periampullary Duodenal Diverticula Are Associated with Occurrence and Recurrence of Bile Duct Stones: A Case-Control Study from a Chinese Center - Zhen Sun; Wenhui Bo; Ping Jiang; Quan Sun (Gastroenterology Research and Practice)
Aims. We here investigated the association of different types of periampullary diverticula (PAD) with pancreaticobiliary disease and with technical success of endoscopic retrograde cholangiopancreatography (ERCP). Methods. A total of 850 consecutive patients who underwent their first ERCP were entered into a database. Of these patients, 161 patients (18.9%) had PAD and the age- and sex-matched control group comprised 483 patients. Results. PAD was correlated with common bile duct (CBD) stones (59.6% versus 35.0% in controls; P=0.008) and negatively correlated with periampullary malignancy (6.8% versus 21.5% in controls; P=0.004). The acute pancreatitis was more frequent (62.5%) in patients with PAD type 1 followed by PAD type 2 (28.9%, P=0.017) and type 3 (28.0%, P=0.006). No significant differences were observed in successful cannulation rate and post-ERCP complications among the 3 types of PAD. Type 1 PAD patients had less recurrence of CBD stones than did the patients who had type 2 or type 3 PAD (53.8% versus 85.7%; P=0.043). Conclusions. PAD, especially type 1 PAD, is associated with an increased acute pancreatitis as well as occurrence and recurrence of CBD stones. PAD during an ERCP should not be considered as an obstacle to a successful cannulation.